2013
DOI: 10.1016/j.joca.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional and longitudinal associations between radiographic features and measures of pain and physical function in hand osteoarthritis

Abstract: Radiographic hand OA is associated with tenderness in the same joint, and erosive development strongly predicts future joint tenderness independent of other radiographic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 27 publications
10
77
1
Order By: Relevance
“…Thirty finger joints, including the distal/proximal/thumb interphalangeal, metacarpophalangeal, and first carpometacarpal joints, were scored for global OA severity according to the Kellgren-Lawrence (KL) scale (grade 0-4) (10) by one reader (IKH). The intra-reader reliability was good (weighted kappa ¼ 0.82) (11). One rheumatologist (BS-C) performed a clinical joint examination of all patients, including assessment for tenderness upon palpation in the 30 hand joints.…”
Section: Hand Oa Examinationmentioning
confidence: 99%
“…Thirty finger joints, including the distal/proximal/thumb interphalangeal, metacarpophalangeal, and first carpometacarpal joints, were scored for global OA severity according to the Kellgren-Lawrence (KL) scale (grade 0-4) (10) by one reader (IKH). The intra-reader reliability was good (weighted kappa ¼ 0.82) (11). One rheumatologist (BS-C) performed a clinical joint examination of all patients, including assessment for tenderness upon palpation in the 30 hand joints.…”
Section: Hand Oa Examinationmentioning
confidence: 99%
“…when summed from semi-quantitative CR scores) and self-reported pain at rest or during activities. At joint level, however, a recent study has suggested a positive cross-sectional association between radiographic features of hand OA and hand pain [20], and radiographic progression, especially incident erosions, were associated with incident joint tenderness [20].…”
Section: Radiography Of Hand Oamentioning
confidence: 98%
“…Differences and advantages of X-ray or MRI techniques have been studied [9][10][11][12][13][14], it is important to take into account that in emerging countries the first approach to diagnose knee OA is X-ray imaging, in early stages of OA the use of MRI images in an exploratory stage is not allowed by the monetary cost to the public health systems. This is an important reason to develop a robust prognostic method based on a very extended imaging tool, the X-ray imaging technology.…”
Section: Introductionmentioning
confidence: 99%